2020
DOI: 10.1093/nar/gkaa010
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis reveals a switch in the translational program upon oocyte meiotic resumption

Abstract: During oocyte maturation, changes in gene expression depend exclusively on translation and degradation of maternal mRNAs rather than transcription. Execution of this translation program is essential for assembling the molecular machinery required for meiotic progression, fertilization, and embryo development. With the present study, we used a RiboTag/RNA-Seq approach to explore the timing of maternal mRNA translation in quiescent oocytes as well as in oocytes progressing through the first meiotic division. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 67 publications
8
88
0
Order By: Relevance
“…Indeed, DNA replication and transcription are not taking place during meiotic divisions but only after fertilization, in the embryo. This translational program is well-conserved in mouse prophase-arrested oocytes [76]. However, not all the genes regulating M-phase progression are translationally repressed.…”
Section: Genome-wide Description Of the Prophase Arrest Of Fully-growmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, DNA replication and transcription are not taking place during meiotic divisions but only after fertilization, in the embryo. This translational program is well-conserved in mouse prophase-arrested oocytes [76]. However, not all the genes regulating M-phase progression are translationally repressed.…”
Section: Genome-wide Description Of the Prophase Arrest Of Fully-growmentioning
confidence: 99%
“…Zar2 and CPEB1 act in a similar manner-their degradation is necessary to remove the repression of translation operating in prophase. Using an approach based on 3 -UTR reporters, it has been shown that the removal of the inhibitory complex (de-repression) increases the rate of translation in prophase I-arrested oocytes [76]. Importantly, the translation of these reporters further increases during meiosis resumption, suggesting that the activation of the translation does not simply rely on the de-repression of mRNAs but requires the recruitment of activating complexes [76].…”
Section: The Rbp Network Controlling the Late Wave Of Translationmentioning
confidence: 99%
See 2 more Smart Citations
“…Piqué et al [22] described a code based on the number and relative position of CPEs and PBEs that determined the timing of Cpeb1-mediated translation in frog oocytes. A more recent study defined such a code in mouse oocyte mRNAs whereby the efficiency of translational repression and activation depended on the numbers and positions of CPEs relative to PASs [85]. Differentially timed translation activation can also be mediated by the sequential activation of RBPs, such as has been proposed for DAZL which is thought to be translationally activated during oocyte maturation by CPEB1 [34].…”
Section: Translational Activation After Gvbdmentioning
confidence: 99%